Extending Education Shapes Student Behaviour in Entrepreneurship: The Mediating Role of Self-efficacy and Intention - Suratman, Andriyastuti; Roostika, Ratna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study examines that the entrepreneurship education curriculum process requires other supports, such as self-efficacy and intention from internal students. As 461 respondents were gathered by convenience sampling from a total population of 530 students taking Sharia Entrepreneurship courses at a private Islamic university in Indonesia. Entrepreneurial education does not have a significant direct effect on the formation of entrepreneurial behavior. However, entrepreneurship education can provide motivation for entrepreneurial intentions and make students more self-aware about entrepreneurship. Only after the stages of self-efficacy and intention appear in students can they drive more profound entrepreneurial behavior. The existence of self-efficacy and entrepreneurial intentions is a way that is more reinforcing outside of education as a trigger for entrepreneurial behavior. This result is seen from the direct influence that is not significant between education and behavior; it is fully mediated by self-efficacy and intention. This indicates that entrepreneurial knowledge is only a source of knowledge. If students' internal factors do not support it, then education will only be mere information simply because it is a required subject for students to pursue. It is necessary to have the role of educational institutions to also look at other stimulus factors to shape entrepreneurial behavior, such as aspects of family, gender, passion, and other things that can activate entrepreneurial behavior.